Comparative clinical evaluation of Class V restorations with disperse phase amalgam and Z350 resin - Lahoud Salem, Víctor (2007)
The object of the study was to evaluate the clinical performance of disperse phase amalgam and Z350 resin in Class V restorations. 60 bicuspids and molars were selected with caries without pulp compromise; these were divided in to 2 groups: Group I, 30 restorations class V with disperse phase amalgam, Group II, 30 restorations class V with resin Z350. We evaluated in each restoration: marginal adaptation, secondary caries, and post-operative sensibility. The results showed 100% success related to marginal integrity and carious recurrence. There was not post operative sensibility, after 06 months of evaluation in 60 treated cases.